PERBEDAAN PENERAPAN MANAJEMEN STRES PADA LANSIA YANG TINGGAL DI PANTI DAN LANSIA YANG TINGGAL DENGAN KELUARGA - Afriani, Neneng Tri; Bidjuni, Hendro; Larira, Dina Mariana (Universitas Sam Ratulangi, 2021)
Abstract Background: Over a period of almost 5 decades, the percentage of Indonesia's elderly population has doubled where the increase in the elderly population has become a global phenomenon. Most of the elderly who live in nursing homes experience stress, while the elderly who live with their families do not experience stress, so stress management for each elderly is generally different. Aim: To find out the difference in the application of stress management for the elderly in nursing homes and those who live with their families. Method: The research method is descriptive analytic with a cross sectional approach where the researcher measures the difference between stress management for the elderly in nursing homes and the elderly with their families. Result: Stress management for the elderly at BPLU Senja Bright Paniki that of 45 respondents found 31 elderly doing good stress management while 14 elderly doing enough stress management, stress management for the elderly at the peaceful orphanage Ranomuut of 13 respondents found 5 elderly doing good stress management while 8 elderly doing adequate stress management, and stress management for the elderly with their families, it was found that from 50 respondents, 34 elderly people did good stress management while 16 elderly did poor stress management. Conclusion: There are differences in the application of stress management for the elderly who live in orphanages and the elderly who live with their families.Keywords: stress management, elderly, nursing home, familyAbstrak: Latar Belakang: Selama kurun waktu hampir 5 dekade, presentasi penduduk lansia Indonesia meningkat dua kali lipat dimana meningkatnya populasi lansia menjadi fenomena global. Sebagian besar lansia yang tinggal di panti werdha mengalami stress sedangkan lansia yang tinggal dengan keluarga sebagian besar tidak mengalami stress sehingga manajemen stress setiap lansia umumnya berbeda. Tujuan: Untuk mengetahui perbedaan penerapan manajemen stress lansia di panti dan yang tinggal dengan keluarga. Metode: Metode penelitian deskriptif analitik dengan pendekatan cross sectional dimana peneliti mengukur perbedaan di antara manajemen stress lansia di panti dan lansia dengan keluarga. Hasil: Manajemen stres lansia di BPLU Senja cerah paniki bahwa dari45 responden didapati 31 lansia melakukan manajemen stress yang baik sedangkan 14 lansia melakukan manajemen stress yang cukup, manajamen stress lansia di panti damai ranomuut dari 13 responden didapati 5 lansia melakukan manajemen stress yang baik sedangkan 8 lansia melakukan manajemen stress yang cukup, dan manajemen stress lansia dengan keluarga didapati bahwa dari 50 responden didapati 34 lansia melakukan manajemen stress yang baik sedangkan 16 lansia melakukan manajemen stress yang buruk. Kesimpulan: Terdapat perbedaan penerapan manajemen stress lansia yang tinggal di panti dan lansia yang tinggal dengan keluarga.Kata kunci: manajemen stress, lansia, panti werdha, keluarga